Mapping Inequalities in Local Political Representation: Evidence from Ohio School Boards. (December 2018) - Bartanen, Brendan; Grissom, Jason A.; Joshi, Ela; Meredith, Marc
Elected representatives' place of residence can reveal information about their socioeconomic status, their likely social networks, and potential biases in the constituencies they represent. Using data on home addresses we collected from local elections offices, we investigate the geographic distribution of school board candidates', including winners', places of residence across two election cycles for 610 school districts in Ohio. We employ geographic information systems (GIS) to identify census block group and school enrollment zones associated with each candidate's residence. We document differences among block groups and schools with more and less school board representation, including a robust association between the relative affluence of a neighborhood and the likelihood of school board members residing in that area. We find that more citizens from affluent areas run for school board, and because a large proportion of school board elections feature minimal competition, these higher propensities to run explain disparities in representation.